PEMBERDAYAAN MASYARAKAT DALAM DETEKSI DINI STUNTING PADA KADER POSYANDU DAN IBU BALITA DI WILAYAH KERJA PUSKESMAS KARAWANG KABUPATEN KARAWANG - Sugiri, Herry; Fariji, A. Achmad (Poltekkes Kemenkes Bandung, 2024)
Karawang Regency is included in the 14 districts that are the LOCUS for intervention in reducing stunting rates in West Java. Meanwhile, Karawang Regency itself has a Nutrition Status Monitoring Locus (PSG) area, namely ten Community Health Center Working Areas (Profile of the Karawang Regency Health Office, 2018). The Karawang District Health Service reported that the number of residents in this area experiencing stunting reached 12 percent. Meanwhile, the population of the region called the base city of this struggle is more than 2.2 million people. In this way, there are around 264 thousand people with stunting problems in the Karawang area (Profile of Karawang District Health Office, 2018). Karang Pawitan sub-district is the city center/government center which has health facilities (Puskesmas Karawang), educational facilities (SMPN, SMA/SMKN, and training institutions/courses) and a large field (Karang Pawitan Field) where large events/ceremonies are held organized by the Regional Government, also close to entertainment facilities, shopping centers, fast food restaurants and so on. So, this area is very vital not only for the people of Karawang City, but also for Karawang Regency. The aim of implementing community service is to increase the knowledge of Posyandu cadres and mothers in the Karawang Community Health Center working area regarding early detection of stunting. The implementation of community service at the Karawang Community Health Center began with coordination with the head of the Community Health Center on May 31, 2023. The results of community service activities showed that there was an increase in the knowledge of Posyandu cadres about early detection of stunting and an increase in the knowledge of mothers with toddlers about early detection of stunting.